2021
DOI: 10.1371/journal.pone.0247258
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observational study and serosurvey of SARS-CoV-2 infection in asymptomatic healthcare workers at a Canadian tertiary care center

Abstract: Health care workers (HCWs) are at higher risk for SARS-CoV-2 infection and may play a role in transmitting the infection to vulnerable patients and members of the community. This is particularly worrisome in the context of asymptomatic infection. We performed a cross-sectional study looking at asymptomatic SARS-CoV-2 infection in HCWs. We screened asymptomatic HCWs for SARS-CoV-2 via PCR. Complementary viral genome sequencing was performed on positive swab specimens. A seroprevalence analysis was also performe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…Ten studies did not report the age of the participants. Only 15 studies reported the median age [39, 47, 57, 59, 61, 64, 86, 107, 118, 121, 123, 124, 127, 137, 145] and only 21 studies reported the sex distribution of people with asymptomatic SARS-CoV-2 [39, 40, 46, 48, 50, 57, 59, 61, 63, 64, 72, 86, 87, 107, 113, 118, 121, 123, 124, 127, 137] (Table 1, S2 Table). The types of included studies changed across the four versions of the review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies did not report the age of the participants. Only 15 studies reported the median age [39, 47, 57, 59, 61, 64, 86, 107, 118, 121, 123, 124, 127, 137, 145] and only 21 studies reported the sex distribution of people with asymptomatic SARS-CoV-2 [39, 40, 46, 48, 50, 57, 59, 61, 63, 64, 72, 86, 87, 107, 113, 118, 121, 123, 124, 127, 137] (Table 1, S2 Table). The types of included studies changed across the four versions of the review.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst all 130 included studies, 88 studies used more than one method of follow-up to ascertain asymptomatic status (Table 1, S2 Table). Only 22 of 130 studies reported the median or mean age [38,47,70,76,77,83,85,95,99,119-121,124,126,128,133,134,139,143,146,152,164] and only five studies included children only [65,67,110,115,118]. Only 31 studies reported the sex of people with asymptomatic SARS-CoV-2 (Table 1, S2 Table) [38,47,51,53,70,71,75,76,83,85,95,99,107,119-122,124,126,128,133,134,139,143,146,147,150,153,158,162,164].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that asymptomatic carriers are able to spread infection (Ooi andLow, 2020, Rasmussen andPopescu, 2021). In an observational study from Canada, symptomatic SARS-CoV-2 infection in HCWs was found to be more common than asymptomatic, and only 0.50% of the asymptomatic participants were PCR-positive (Ferreira et al, 2021). In our study, 12.3% of seropositive HCWs did not report any symptoms, highlighting that although asymptomatic infections are infrequent, they may cause outbreaks among both patients and co-workers.…”
Section: Discussionmentioning
confidence: 99%
“…This figure is 4.1% for HCWs of wards with patients with respiratory symptoms without laboratory evidence of SARS-CoV-2 positivity [8]. Reports of antibody positivity in HCW cohorts early in the pandemic ranged widely across studies, hospitals, and geographic settings from 3.4-1.4% in a large Canadian tertiary care center [9], 3.2% in an oncology department of an Austrian university hospital [10], to just 1% in a Californian regional health-care delivery network [11]. To date, there are no published data indicating the incidence of asymptomatic positive COVID-19 HCWs employed at a center dedicated exclusively to the treatment of cancer patients.…”
Section: Introductionmentioning
confidence: 99%